Analysis of Quality Property Variations in Commercial Candied Strawberries - Liying NIU; Jian CHEN; Rui WANG; Rongrong HE; Zhongyuan ZHANG; Chunju LIU; Yadong XIAO; Meimei NIE; Dajing LI (Shipin gongye ke-ji, 2024)
The purpose of this study was to discover the quality properties of the commercially available candied strawberries. Fifteen samples with different brands were purchased, and the physicochemical parametes, such as color, texture, sugar and acid content were determined using colorimeter, texture analyzer and HPLC. In addition, sensory scores were evaluated using intensity scale method. The results showed that the moisture content of these preserved strawberries were between 12.49% and 23.86%, and the colorimetric values distribution ranges of L*, a* and b* were 23.25~34.39, 5.17~19.83, and 5.78~17.04, respectively. For the texture characters, there were significant differences (P<0.05) in hardness, chewiness, and adhesive force between the samples. Fructose and glucose were the major soluble sugars in the samples, and they contributed 30.17%~52.43% and 28.49%~55.15% for the total sugars, respectively. While less content of sucrose and maltose were detected, which contributed 0.00%~33.00% and 0.00%~14.08% for the total sugars. Moreover, citric acid and malic acid were the main organic acids, and their contents were 7.98~13.05 mg/g and 4.48~8.17 mg/g, respectively. For the sensory scores, color, viscosity, and overall acceptance showed larger dispersions. Using double-way cluster analysis, the samples were separated as two clusters and the quality properties were clustered into three groups. The samples in cluster I obtained higher values of a*, b*, and springiness, as well as higher sensory scores of color, viscosity, and overall acceptance, which separated them with the samples in cluster II, illustrating that the quality difference of the candied strawberries were focused on the color and texture characters. In addition, the clustered results of the quality parameters showed that close relationships among citric acid, glucose and fructose content with chewiness. Similarly, maltose, sucrose and water content associated with the viscosity. These study results provided a direction for the quality discrimination and control of candied strawberries.